Polycystic ovarian syndrome elevates the distress of sexual pain in Iranian women with infertility - Bita Tahmasbi; Reza Eshraghi; Mohammadali Amini-Tehrani; Hadi Zamanian; Ashkan Ilami (BMC, 2024)
Abstract Background Sexual dysfunction may lead to sexual distress in women with infertility, while polycystic ovarian syndrome (PCOS) may escalate this distress. This study aimed to investigate the role of PCOS in the relationship between sexual dysfunction and sexual distress in Iranian women with infertility. Methods The Female Sexual Function Index (FSFI), Female Sexual Distress Scale-Revised (FSDS-R), and Depression and Anxiety modules of the DASS-21 were cross-sectionally investigated in 190 women with infertility (103 women with PCOS and 87 women without PCOS). Results There were negative correlations between sexual function domains and sexual distress (P < .001) in the total sample. Moderation analysis revealed that higher levels of impaired desire, arousal, and pain elevated sexual distress in the PCOS group. After adjusting for depression and anxiety, only the association between sexual pain and sexual distress was moderated by PCOS condition (P = .008). Conclusions The findings suggest that impaired sexual function is associated with increased levels of sexual distress in infertile female patients. Importantly, comorbid PCOS renders patients susceptible to sexual distress where sexual pain is increased. Further research may shed light on the physiological, psychological, and relational aspects of sexual pain and associated distress in infertile female patients with comorbid PCOS.